The holy spirit in the Qur'an : an assessment from a Christian perspective - Shih-Ching, Judy Tao; Tau Shih-Ching, Judy (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2006.